L’Atlantide ou la quête de l’absence. D’un pays sans amour de Gilles Rozier - Żurawska, Anna (Romanica Silesiana)
The novel D’un pays sans amour (2011) by Gilles Rozier features two narrators who try to recapture the past and to reconstruct with letters the Yiddishland annihilated after World War II. This vanished state, with its cultural capital situated in Warsaw, is called Atlantis in the novel and presented as a paradise in the yiddish literature and language. The choice of this metaphor encourages the reflection on the ambivalence between reality and fiction, as well as on the oppositions between presence and absence or memory and oblivion. What is more, this metaphor refers to the categories of time and space. The aim of this article is to examine the function of the Atlantis metaphor on which the novel is based and to analyze the mechanisms of narrative as memorial (on the basis of Paul Ricœur’s concept) which allow the narrator to rebuild the annihilated world of the mythical island and to bring the non‑existent back into existence. Key words: Atlantis, mythical island, the yiddish literature and language, presence / absence, memory / oblivion, time and space